2018
DOI: 10.1017/s175173111700249x
|View full text |Cite|
|
Sign up to set email alerts
|

Which is the most preventive measure against tail damage in finisher pigs: tail docking, straw provision or lowered stocking density?

Abstract: One challenge of intensive pig production is tail damage caused by tail biting, and farmers often decrease the prevalence of tail damage through tail docking. However, tail docking is not an optimal preventive measure against tail damage and thus, it would be preferable to replace it. The aim of the current study was to investigate the relative effect of three possible preventive measures against tail damage. The study included 112 pens with 1624 finisher pigs divided between four batches. Pens were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…However, under our experimental conditions, other factors may have helped preventing tail lesions, such as high space allowance, low number of pigs per pen, presence of environmental enrichments and stability of the groups. For example, Di Martino et al (2015) observed increased tail lesions when undocked pigs were kept under challenging conditions (high stocking density on fully slatted floors) even if the pens were enriched with straw racks suggesting a possible major role played by space allowance, or at least by a complex combination of these two factors (Larsen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, under our experimental conditions, other factors may have helped preventing tail lesions, such as high space allowance, low number of pigs per pen, presence of environmental enrichments and stability of the groups. For example, Di Martino et al (2015) observed increased tail lesions when undocked pigs were kept under challenging conditions (high stocking density on fully slatted floors) even if the pens were enriched with straw racks suggesting a possible major role played by space allowance, or at least by a complex combination of these two factors (Larsen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The design and dimensions of the pens can be seen in Figure 1. As part of a larger study design (Larsen et al, 2018) and to test whether TS in pigs depends on different potential environmental pen level stressors, the pens were randomly divided within each batch between one level of each of three factors in a 2 × 2 × 2 factorial design: 1) TAIL: pigs with undocked (n=36) or docked tails (n=44), (2) STRAW: not provided with straw (n=40) or provided with 150 g of straw per pig per day on the solid floor (n=40), (3) STOCK: stocking density of 0.73 m 2 /pig (n=40, 18 pigs per pen, high) or 1.21 m 2 /pig (n=40, 11 pigs per pen, low). Fewer pens with undocked pigs compared to pens with docked pigs were included due to many of the undocked pigs arriving from a private herd shortly after weaning with bleeding tails in batch 2 and thus not included in the study.…”
Section: Animal Housing and Managementmentioning
confidence: 99%
“…Thus, it could also be expected that pens with straw provided in the current study would have a lower degree of TS. Perhaps the variation in the induced stressors was not large enough relative to the overall stress level in the pens to show an effect on TS, although they did increase the risk of tail damage (Larsen et al, 2018). On the other hand, both provision of straw and a higher stocking density may affect the dirtiness of the pen and pigs, especially towards the end of the finisher period (Larsen et al, 2017).…”
Section: The Relation To Pen-level Stressorsmentioning
confidence: 99%
“…Also, temperature measurements of the strawbedded area might also prove effective in predicting events of fouling, which has already been shown for temperature measurements at other locations of the pen (Jensen and Kristensen, 2016). Straw has been shown to have other positive effects for slaughter pigs such as reducing the risk of tail biting (Van de Weerd et al, 2005;Scollo et al, 2013;Larsen et al, 2017a) and gastric ulceration (Di Martino et al, 2013;Herskin et al, 2016;Jensen et al, 2017), improving growth rate (Pedersen et al, 2015) and increasing the expression of species-specific behaviour such as exploration (Jensen et al, 2015). Thus, it is desirable to be able to provide straw or enrichment with similar properties without increasing the risk of fouling, and, according to our study, provision of straw was not a major risk factor.…”
Section: The Effect Of Straw Provisionmentioning
confidence: 91%
“…This study uses the same animals as Larsen et al (2017a), and further details about the experimental setup can be found there.…”
Section: Methodsmentioning
confidence: 99%